2021
DOI: 10.3389/fgene.2021.657970
|View full text |Cite
|
Sign up to set email alerts
|

New Insights Into Structure and Function of TIFY Genes in Zea mays and Solanum lycopersicum: A Genome-Wide Comprehensive Analysis

Abstract: The TIFY gene family, a key plant-specific transcription factor (TF) family, is involved in diverse biological processes including plant defense and growth regulation. Despite TIFY proteins being reported in some plant species, a genome-wide comparative and comprehensive analysis of TIFY genes in plant species can reveal more details. In the current study, the members of the TIFY gene family were significantly increased by the identification of 18 and six new members using maize and tomato reference genomes, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 98 publications
2
30
0
Order By: Relevance
“…The variations in subcellular localization may occur due to various factors, such as proteinprotein interaction and post-translational modifications [36,64]. The prediction of 3D structure and pocket site of proteins can provide valuable information about protein function based on ligand-binding sites [65,66]. In the present study, the cysteine, proline, lysine, leucine, serine, and threonine were frequently predicted as the key binding residues in the structure of GASA proteins, in which proline, serine, and leucine are known as the amino acid residues associated with responses to environmental stimuli [65,67].…”
Section: Discussionmentioning
confidence: 99%
“…The variations in subcellular localization may occur due to various factors, such as proteinprotein interaction and post-translational modifications [36,64]. The prediction of 3D structure and pocket site of proteins can provide valuable information about protein function based on ligand-binding sites [65,66]. In the present study, the cysteine, proline, lysine, leucine, serine, and threonine were frequently predicted as the key binding residues in the structure of GASA proteins, in which proline, serine, and leucine are known as the amino acid residues associated with responses to environmental stimuli [65,67].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, MGTs have been speculated to regulate the downstream pathways related to response to abiotic stresses by interacting with Ca 2+ sensors [83]. Our findings revealed that the MGT duplicated gene pair could have diverse expression patterns, suggesting that these genes probably under some modifications or insertion/deletion in their sequence, CDS, or promoter regions have received novel functions [71,84]. Modifications, such as gains and losses of cis elements in promoters between duplicated gene pairs, e.g., parent and daughter genes, could occur after duplication events, affecting the expression levels [85,86].…”
Section: Discussionmentioning
confidence: 82%
“…In previous studies, 62 MGTs in Camelina sativa [12], 41 MGTs in Triticum turgidum [12], 12 MGTs in Zea mays [70], 16 MGTs in Pyrus bretschneideri [23], 36 MGTs in Brassica napus [25], 12 MGTs in Fagaria vesca [27], and 8 MGTs in Poncirus trifoliata [24] were characterized. The number of MGTs is probably correlated with polyploidy events and genome size [12,71]. The prediction of the pI value of MGT proteins illustrated that CcMGTs are more acidophilic proteins than TcMGTs and GhMGTs, indicating that CcMGTs are mostly active under acidic conditions (pI < 6.50).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the alteration of membrane conformation can cause oxidative stress by rapidly inducing reactive oxygen species (ROS), and then, the concentration of cryoprotective compounds increases in the cytoplasmic matrix [2,6,7]. However, plants use various mechanisms, including morphological and structural modifications, as well as biochemical mechanisms to modulate cellular homoeostasis to reduce low, nonfreezing temperature-induced damage [2,8,9]. Approximately 10% of the genes in Arabidopsis are involved in the response to cold stress and are known as cold-regulated (COR) genes [10,11].…”
Section: Introductionmentioning
confidence: 99%